Thiosemicarbazone derivatives, thiazolyl hydrazones, effectively inhibit leukemic tumor cell growth: Down-regulation of ribonucleotide reductase activity and synergism with arabinofuranosylcytosine. (October 2017) - Graser-Loescher, Geraldine; Schoenhuber, Agnes; Ciglenec, Caroline; Eberl, Sabine; Krupitza, Georg; Mader, Robert M.; Jadav, Surender S.; Jayaprakash, Venkatesan; Fritzer-Szekeres, Monika; Szekeres, Thomas; Saiko, Philipp
Abstract: Cellular growth inhibition exerted by thiosemicarbazones is mainly attributed to down-regulation of ribonucleotide reductase (RNR) activity, with RNR being responsible for the rate-limiting step of de novo DNA synthesis. In this study, we investigated the antineoplastic effects of three newly synthesized thiosemicarbazone derivatives, thiazolyl hydrazones, in human HL-60 promyelocytic leukemia cells. The cytotoxicity of compounds alone and in combination with arabinofuranosylcytosine (AraC) was determined by growth inhibition assays. Effects on deoxyribonucleoside triphosphate (dNTP) concentrations were quantified by HPLC, and the incorporation of radio-labeled 14 C-cytidine into nascent DNA was measured using a beta counter. Cell cycle distribution was analyzed by FACS, and protein levels of RNR subunits and checkpoint kinases were evaluated by Western blotting. VG12, VG19, and VG22 dose-dependently decreased intracellular dNTP concentrations, impaired cell cycle progression and, consequently, inhibited the growth of HL-60 cells. VG19 also lowered the protein levels of RNR subunits R1 and R2 and significantly diminished the incorporation of radio-labeled 14 C-cytidine, being equivalent to an inhibition of DNA synthesis. Combination of thiazolyl hydrazones with AraC synergistically potentiated the antiproliferative effects seen with each drug alone and might therefore improve conventional chemotherapeutic regimens for the treatment of human malignancies such as acute promyelocytic or chronic myelogenous leukemia. Graphical abstract: Highlights: All compounds decreased deoxyribonucleoside triphosphate concentrations. Replication stress was followed by cell cycle arrest and growth inhibition. VG19 lowered the protein levels of ribonucleotide reductase subunits R1 and R2. VG19 diminished the incorporation of radio-labeled 14 C-cytidine into DNA. Combination with AraC synergistically potentiated the antiproliferative effects.